Technology Adoption by Microentrepreneurs: A 2018-2023 Literature Review - Barbosa Guerrero, Lugo Manuel; González García , Leidy Yolanda (Journal of Ecohumanism, 2024)
The purpose of this review is to identify and analyze the processes of technological adoption by microentrepreneurs through a comprehensive literature review. Employing a mixed, non-experimental, and exploratory descriptive methodology, a literature review matrix was used to systematize selected high-impact scientific articles from the Scopus database, with 50 articles chosen for content analysis. The main findings reveal nine theoretical trends that define the primary themes in this field of study, highlighting key characteristics, advantages, and weaknesses of technological adoption by microentrepreneurs across various sectors. Additionally, a significant number of research tools were identified and categorized into three paradigms: quantitative, qualitative, and mixed. Current perspectives and emerging patterns related to technology adoption were examined, emphasizing factors such as individual attitudes, resource availability, and training effectiveness. This literature review contributes to discussions on the dynamics, challenges, and opportunities in technology adoption by microentrepreneurs, providing a comprehensive overview of existing research, highlighting areas of interest, and fostering an understanding of the complexities surrounding technology adoption. The findings offer valuable insights for policymakers, educators, and practitioners aiming to support microentrepreneurs in their technological endeavors, emphasizing the need for continued research to address evolving challenges and leverage opportunities presented by technological advancements.